RELATIONSHIP OF TRANSVERSAL ASYMMETRIC FACE AND UNILATERAL POSTERIOR CROSSBITE - Indah Dwinursanty; Krisnawati Krisnawati; Maria Purbiati (Faculty of Dentistry, Universitas Indonesia, 2006)
Unilateral posterior crossbite is commonly seen in mixed dentition, but it couldn't be self corrected. If this condition is not treated properly, it could lead to asymmetric face. Asymmetric face with unilateral posterior crossbite could make the treatment process more difficult. The objective of this study is to find out the relationship between transversal skeletal asymmetry and unilateral posterior crossbite. Patients older than 13 years with skeletal asymmetric face, who had never undergone orthodontic treatment or facial surgery were selected. The sample consisted of 15 females and 6 males (15 - 32 years old). Anteroposterior cephalogram was used for determining the difference between right and left of antegonial and the deviation of menton. Criteria for asymmetry were more than 3 mm on Antegonial and 2 mm or more on Menton. Mid Sagital Reference (MSR) was used as reference line. Unilateral posterior crossbite could be seen in the dental model. The data was analyzed using Mann Whitney test. It was revealed that from 21 samples, 38.1% was found to have unilateral posterior crossbite involving four posterior teeth. Conclusion: There is no relationship between transveral skeletal symmetry and unilateral posterior crossbite.